Distingsi antara Hadis, Sunnah, Khabar, dan Atsar: Sebuah Telaah Konseptual dan Perbedaan dalam Perspektif Ulama - Lesna Tarida; Muhammad Fatchullah; Azhary, Muhammad Royyan Faqih; Advan Navis Zubaidi (Almustofa Journal of Islamic Studies and Research, 2025)
This study examines the conceptual distinctions between the key terms "Hadith," "Sunnah," "Khabar," and "Atsar" within the science of Hadith. While often used interchangeably in Islamic scholarship, these terms carry nuanced differences that have significant methodological implications for hadith research, verification, and transmission. Employing a qualitative approach through library research and descriptive-analytical methods, this study analyzes authoritative classical and contemporary texts to map the definitions, scopes, and scholarly debates surrounding each term. The findings reveal that "Hadith" is the most specific term, strictly referring to narrations attributed to the Prophet Muhammad (SAW). "Sunnah" has a broader scope, encompassing the Prophet's continuous practice, character, and life journey, and is heavily emphasized in legal theory (Usul al-Fiqh). "Khabar" is a more general term for "news," which, according to various scholarly opinions, can be synonymous with Hadith, refer specifically to non-prophetic reports, or encompass both. "Atsar" predominantly refers to narrations from the Companions and Successors, though it is sometimes used synonymously with Hadith. The research concludes that the semantic complexity and diverse scholarly perspectives on these terms are not merely academic but fundamentally impact the methodology of hadith studies and Islamic legal derivation. A precise understanding of these distinctions is therefore crucial for the integrity and depth of contemporary Islamic research.